LEGAL STUDY OF FIDUCIARY GUARANTEE LAW IN THE PERSPECTIVE OF ISLAMIC LAW AND LAW NO. 42 OF 1999 CONCERNING FIDUCIARY GUARANTEE IN INDONESIA - Maulana, Ayang Fristia; Irwanto, Irwanto; Surya, Jaka; LZ, Mili Niko Tari Buah; Nazara, Mebu’aro Fosawato (MIZAN: JOURNAL OF ISLAMIC LAW, 2024)
The law of guarantees recognizes two types of guarantees, namely general guarantees and special guarantees, while special guarantees can still be distinguished into material guarantees and guarantees of people who guarantee debts. General guarantees and debt guarantees do not fully provide certainty regarding debt repayment, because the creditor does not have priority rights so the creditor's position remains as a concurrent creditor against other creditors. Fiduciary guarantees are conventional products that are determined to protect creditors, especially if the debtor defaults. Fiduciary guarantees that have not been able to be applied comprehensively to all financial institution systems in Indonesia, need to be conducted several studies, especially from the perspective of Islam and Law No. 42 of 1999 which uses the Sharia financial system. The focus of the study that is used to formulate the problem is how is the law of fiduciary guarantees from the perspective of Islamic law and Law No. 42 of 1999 concerning fiduciary guarantees in Indonesia. In this study, normative law is used, or it can be called library research. The results of the study show that the practice of implementing fiduciary in Indonesia has a very important position and must be fulfilled by financing service providers. Meanwhile, according to Islamic views, there is no fiduciary guarantee in the aspect of Islamic law, but matters concerning guarantees can be equated with Rahn. Thus, in Islamic Financial Institutions, Rahn is guided as a guarantee system in lending activities by Islamic law, this is based on the word of Allah QS. Al-Baqarah verse 283 and Law Number 21 of 2008 concerning Islamic Banking.